2020
DOI: 10.1098/rsta.2019.0587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of detectability of differential type probe using directional eddy current for fibre waviness in CFRP

Abstract: This paper describes the detectability of eddy current testing (ECT) using directional eddy current for detection of in-plane fibre waviness in unidirectional carbon fibre reinforced plastic (CFRP) laminate. Three different types of probes, such as circular driving, symmetrical driving and uniform driving probe, were proposed, and the waviness angle was extracted from the contour map of the ECT signal by applying a Canny filter and a Hough transform. By comparing both the waviness angle estimated by ECT and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Furthermore, _ U R _ I can be used to characterize the eddy current loss. Equation (15) indicates that the power of the magnetic flux of the primary magnetic field passing through the sensor is 0; therefore, using _ U R _ I to characterize the eddy current loss shields the interference of the primary magnetic field.…”
Section: Measurement Of Eddy Current Loss Using the New Probementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, _ U R _ I can be used to characterize the eddy current loss. Equation (15) indicates that the power of the magnetic flux of the primary magnetic field passing through the sensor is 0; therefore, using _ U R _ I to characterize the eddy current loss shields the interference of the primary magnetic field.…”
Section: Measurement Of Eddy Current Loss Using the New Probementioning
confidence: 99%
“…1 Several studies have reported on the inspection of CFRPs based on the ECT method. [14][15][16] The unidirectional layer of CFRP exhibits strong anisotropic conductivity, resulting in extremely low bulk conductivity that is three orders of magnitude smaller than that of other materials. 17 As this weakens the induced eddy current, the detection signal is considerably low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial body of research has been dedicated to the optimization of EC probes, with various studies focusing on enhancing their efficacy in diverse applications. In an exploration of the efficacy of ECT for in-plane fiber waviness detection in unidirectional carbon fiber reinforced plastic (CFRP), [21] employed a diverse set of probes: circular driving, symmetrical driving, and uniform driving. This study is distinguished by its methodical comparative analysis and the integration of sophisticated image processing techniques, including the Canny filter and Hough transform, to ascertain the probes' precision and accuracy against X-ray CT imaging benchmarks.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Na Zhang and Hiroyuki improved the detection ability of the probe for micro-defects inside CFRPs by utilizing differential probes that can suppress common mode noise and implementing a series of signal processing algorithms. [15,16] Others are committed to enhancing the signal intensity of the receiving coil. For example, Wu et al developed a high-frequency PCB-based TR probe and clearly detected the fiber orientation in unidirectional CFRP plate at frequencies up to 40 MHz.…”
Section: Introductionmentioning
confidence: 99%